Assessment of chicken intestinal hydrolysates as a new protein source to replace fishmeal on the growth performance, antioxidant capacity and intestinal health of common carp (Cyprinus carpio). Issue 125 (June 2022) - Wu, Di; Zhang, Yuanyuan; Li, Jinnan; Fan, Ze; Xu, Qiyou; Wang, Liansheng
Abstract: Promoting circular economy by transforming food residues into alternative high-value protein sources for aquaculture feed is a new way to develop alternative raw materials for fishmeal. This study systematically evaluated the effects of chicken intestinal hydrolysates (CIH) on the intestinal immune health of common carp through growth performance, antioxidant capacity, and intestinal immunity analysis in order to replace fishmeal. Five iso-nitrogenous and iso-lipidic experimental feeds were formulated to replace 0% (CIH-0), 25% (CIH-25), 50% (CIH-50), 75% (CIH-75) and 100% (CIH-100) of the fishmeal with CIH. Each experimental diet was fed to triplicate groups of 30 carp for 8 weeks. The results revealed that no significant differences in the final body weight, weight gain rate, feed coefficient radio, feed intake and protein efficiency ratio were found among the CIH-0, CIH-25, and CIH-50 groups, while the final body weight and weight gain rate in the CIH-75 and CIH-100 groups were significantly decreased and the feed coefficient radio was significantly increased. The aspartate aminotransferase of all CIH groups were significantly decrease, and the total protein, albumin did not differ among the CIH-0, CIH-25, CIH-50, and CIH-75 groups. The trypsin content was significantly increased in the CIH-75 and CIH-100 groups. No significant differences in the antioxidant index (catalase, glutathione peroxidase and malonaldehyde) were found among all CIH groups compared with the CIH-0 group. The expression levels of pro-inflammatory cytokines IL-1β and TNF-α were significantly down-regulated in the CIH-50 group and anti-inflammatory cytokines IL-10 and TGF-β2 were significantly up-regulated in the CIH-50 and CIH-75 groups. No significant differences in the expression levels of claudin-1, claudin-7 and claudin-11 were observed between the CIH-0 and CIH-50 groups, while the expression levels of ZO-1, occludin and MLCK were significantly up-regulated in the CIH-50 group compared with the CIH-0 group. The expression level of claudin-1 was down-regulated in the CIH-75 and CIH-100 groups. Hence, the study demonstrated the potential of CIH as a novel protein source for replacing fishmeal, and replacing 50% of fishmeal with CIH did not significantly influence the growth performance, immune responses, and intestinal barrier of common carp ( Cyprinus carpio ). Highlights: Chicken intestinal hydrolysates (CIH) has a large amount of protein and has the potential to replace fishmeal. CIH can replace fishmeal at up to 50% rate. Partial CIH replacement seemed to enhance the intestinal health by activating the NF-κB/MyD88/MLCK pathway.